An efficient synthesis of dibenzocycloocta-4a,6a,-diene-5,11-diyne and its precursors - Chaffins, Sterling; Brettreich, Michael; Wudl, Fred (Synthesis-Stuttgart, 2002)
Two efficient syntheses of dibenzocyclooctadienediyne 1 were developed employing known reactions, which utilize commercially available reagents. Both methods are an improvement on known syntheses resulting in 41% and 43% overall yields. The latter method also offers an efficient synthesis of dibenzocyclooctatetraene 9, which is one of the key reagents now commercially unavailable.
Keywords: dibenzocyclooctadienediyne; elimination; lithium; sonication